Evaluasi Kebutuhan Tenaga ATC di Bandara Sultan Hasanuddin Makassar - Siti Masrifah (WARTA ARDHIA, 2010)
By looking at the growth of air transport has increased quite significantly, certainly not independent human resources needs to guide them in Air Traffic Control personnel. In this case one of the problems encountered in field of aviation is the imbalance between supply and demand on Ihe one hard, the growth of air transport have increased and on one side of the energv needs of ATC is not in accordance with the operation of the flight. In connection with this case was the result of the ability of the Aviation safety Techical Academy, in terms of manpower needs in Particular ATC Sultan Hasanuddin Airport in Makassar, which now number 144 ATC personel, whereas the ideal number to 145 people personnel. However, the results of estimates / projections for 2015 amounted to 182 personnel required by the ATC.